Online Learning Satisfaction in Philippine Higher Education: A Structural Equation Modeling - General, Edralin; Valle, Lislee; Batican, Ivy; Baclayon, Joshlen; Colina, Sarah Jane; Graham-Wilberforce, Lynne (FKIP Universitas Lampung, 2023)
Online Learning Satisfaction in Philippine Higher Education; A structural equation modeling. Philippine higher education institutions have utilized online learning to improve instructional delivery. Several studies have demonstrated that online education can be as effective as traditional classroom models. However, only a few studies ventured toward investigating learner satisfaction in the areas of motivation, school climate, and online learning self-efficacy, which provides a different perspective on assessing online learning delivery. A cross-sectional survey evaluating 580 valid responses addressed this gap. Motivation, school climate, and online learning self- efficacy predicted online learning satisfaction. The study examined five hypothesized paths using Partial Least Squares - Structural Equation Modeling. Results highlight the positive impact of motivation, school climate, and online learning self-efficacy on online learning satisfaction. This study shows that online learning satisfaction depends on motivation, school climate, and self-efficacy. Therefore, educational institutions and educators should create an encouraging virtual learning environment to ensure students' satisfaction and overall achievement in online education. Keywords: online learning satisfaction, motivation, school climate, online learning self-efficacy, partial least squares -structural equation modeling.DOI: http://dx.doi.org/10.23960/jpp.v13.i3.202337